Beyond Expectancy Theory: An Integrative Motivational Model from Health Care - Walker, Lawrence R.; Thomas, Kenneth W. (Academy of Management Review, 1982)
Expectancy theory has been criticized for its omission of normative, habitual, and other motivational elements. This paper describes the sources and features of an integrative motivational model from the field of preventive health care that combines expectancy/valence factors with habitual, normative, and conative motivational elements. The model is viewed as having implications for work motivation as well.